Isolation of embryonal carcinoma cell lines that express integrated recombinant genes flanked by the Moloney murine leukemia virus long terminal repeat. - Taketo, M (1985)
We have used a producer NIH 3T3 cell line that secretes, together with the helper Moloney murine leukemia virus (Mo-MuLV), a transducing recombinant virus containing the neomycin-resistance gene linked to the Mo-MuLV long terminal repeat (LTR). By infecting three embryonal carcinoma cell lines, PCC4.aza1R, F9tk-, and Nulli-SCC1, with this recombinant virus, we have isolated many transductant clones that stably express the integrated neomycin-resistance gene. These clonal transductant lines consist of undifferentiated embryonal carcinoma cells as judged by morphology, tumorigenicity in 129/Sv mice, and cell-surface antigenic markers. Analysis of the integrated recombinant viral genes by Southern blot hybridization revealed that some of the lines have single copies, whereas others have multiple copies, probably in multiple sites. Although these transductant lines contained many copies of helper Mo-MuLV integrated in the cellular genome, expression of these helper viruses was not detected either by reverse transcriptase activity or by X-C plaque assay. Two F9tk--derived, G418-resistant transductant lines were superinfected with a second recombinant transducing virus that contains the herpes simplex virus thymidine kinase gene flanked by the Mo-MuLV LTR. The frequency of transduction to yield clones able to grow in hypoxanthine/aminopterin/thymidine medium was similar to that of the parental F9tk- cells. These results suggest that the expression of the neomycin-resistance gene, linked to MoMuLV LTR in the transductant embryonal carcinoma cell clones, is due to a cisacting mechanism(s).